Covering plastic films in greenhouses system: A GIS-based model to improve post use suistainable management. (1st June 2020) - Parlato, Monica C.M.; Valenti, Francesca; Porto, Simona M.C.
Abstract: Yearly, in Europe, more than 1 million tonnes of plastic materials are used in agricultural activities. Among the possible applications, plastic films for protected cultivation practices are highly used worldwide because of the significant advantage deriving from the shortening of the growing period. However, in the absence of a correct policy disposal of plastic films, environmental degradation could take place with serious ecological and economic consequences. In this study, a geographical information system (GIS) - based model to locate and quantify the yearly amount of agricultural plastic waste (APW) coming from crop-shelter coverage used in greenhouses system was put forward and was applied in a study area located in southern Italy, highly characterised by protected cultivation practices. Firstly, the areas with the highest density of crop shelters were mapped, then a suitable index to determine APW amount was computed and applied to obtain heat maps related to covering plastic films. Finally, sensitivity analyses were carried out by varying thickness, lifetime, and density of the covering films of the greenhouses, located in the considered samples. The index ranged between 976 kg ha −1 yr −1 and, 2484 kg ha −1 yr −1 . The results showed that the density of greenhouses and tunnels-greenhouses is still elevated nearby the coastline, highlighting that the guidelines of the territorial plan of the Province of Ragusa concerning the displacement of protected crops from the coast to the internal rural areas were disregarded. Moreover, the GIS-based model results could provide basic information for the analysis of the environmental impact due to transportation of APW. Therefore, these results could offer a suitable tool to improve the correct disposal management of covering plastic films and the related recycle policy. Highlights: A suitable tool to improve the agricultural plastic wastes recovery/reuse was provided. GIS-based method to locate and quantify agricultural plastic wastes was developed. A suitable study area for the methodology validation was chosen. Obtained results could be used for environmental impacts analyses.